Study of Ukrainian Polar Explorers' Psychological Readiness for Extreme Environments at the Antarctic Station - Miroshnychenk, Olena; Pasichnyk, Igor; Voznyuk, Alexander; Kubitskyi, Serhii; Roganova, Marina; Tsvietkova, Hanna; Shorobura, Inna; Bloshchynskyi, Ihor (My University, 2020)
The research is devoted to the study of Ukrainian polar explorers’ psychological readiness for extreme environments of the "Academician Vernadsky" Antarctic station.
Miroshnychenk Olena. Study of Ukrainian Polar Explorers' Psychological Readiness for Extreme Environments at the Antarctic Station / Olena Miroshnychenko, Igor Pasichnyk, Alexander Voznyuk, Serhii Kubitskyi, Marina Roganova, Hanna Tsvietkova, Inna Shorobura, Ihor Bloshchynskyi // International Journal of Human Movement and Sports Sciences. – 2020. – Vol. 8, No. 6. – P. 455–461.
Keywords: Психологічна готовність до екстремальних умов оточуючого середовища, полярників, життя в умовах антарктики, підготовка до екстремального виду діяльності, возрастных груп взрослых; Psychological Readiness for Extreme Environmental Conditions, Polar Explorers, Living in Antarctic Conditions, Training for Extreme Activities, Age Groups of Adulthood; Психологическая готовность к экстремальным условиям окружающей среды, полярники, жизнь в условиях Антарктики, подготовка к экстремальным видам деятельности, возрастные группы взрослых